Divergence of Erv1-associated mitochondrial import and export pathways in trypanosomes and anaerobic protists - Basu, Somsuvro; Leonard, Joanne C; Desai, Nishal; Mavridou, Despoina A I; Tang, Kong Ho; Goddard, Alan D; Ginger, Michael L; Lukeš, Julius; Allen, James W A (Eukaryotic cell, 2013)
In yeast (Saccharomyces cerevisiae) and animals, the sulfhydryl oxidase Erv1 functions with Mia40 in the import and oxidative folding of numerous cysteine-rich proteins in the mitochondrial intermembrane space (IMS). Erv1 is also required for Fe-S cluster assembly in the cytosol, which uses at least one mitochondrially derived precursor. Here, we characterize an essential Erv1 orthologue from the protist Trypanosoma brucei (TbERV1), which naturally lacks a Mia40 homolog. We report kinetic parameters for physiologically relevant oxidants cytochrome c and O(2), unexpectedly find O(2) and cytochrome c are reduced simultaneously, and demonstrate that efficient reduction of O(2) by TbERV1 is not dependent upon a simple O(2) channel defined by conserved histidine and tyrosine residues. Massive mitochondrial swelling following TbERV1 RNA interference (RNAi) provides evidence that trypanosome Erv1 functions in IMS protein import despite the natural absence of the key player in the yeast and animal import pathways, Mia40. This suggests significant evolutionary divergence from a recently established paradigm in mitochondrial cell biology. Phylogenomic profiling of genes also points to a conserved role for TbERV1 in cytosolic Fe-S cluster assembly. Conversely, loss of genes implicated in precursor delivery for cytosolic Fe-S assembly in Entamoeba, Trichomonas, and Giardia suggests fundamental differences in intracellular trafficking pathways for activated iron or sulfur species in anaerobic versus aerobic eukaryotes.
Keywords: Cytochromes c; Mitochondria; molekulární evoluce; transport proteinů; Amino Acid Substitution; Phylogeny; Protozoan Proteins; Protein Transport; Evolution, Molecular; oxidace-redukce; cytochromy c; oxidancia; genový knockdown; mitochondrie; mutageneze cílená; Mitochondrial Proteins; Trypanosoma brucei brucei; Mitochondrial Swelling; mitochondriální proteiny; Gene Knockdown Techniques; oxidoreduktasy; Protein Folding; Oxygen; kyslík; Kinetics; zduření mitochondrií; substituce aminokyselin; sbalování proteinů; fylogeneze; RNA Interference; Oxidants; Oxidation-Reduction; Mutagenesis, Site-Directed; Oxidoreductases; RNA interference; protozoální proteiny; kinetika